Continuous aspiration of subglottic secretions in the prevention of ventilator-associated pneumonia in the postoperative period of major heart surgery - Bouza, Emilio; Pérez, María Jesús; Muñoz, Patricia; Rincón, Cristina; Barrio, José María; Hortal, Javier (Chest, 2008)
Aspiration of endotracheal secretions is a major step in the prevention of ventilator-associated pneumonia (VAP). We compared conventional and continuous aspiration of subglottic secretions (CASS) procedures in ventilated patients after major heart surgery (MHS). Randomized comparison during a 2-year period. A total of 714 patients were randomized (24 patients were excluded from the study; 359 CASS patients; 331 control subjects). The results for CASS patients and control subjects (per protocol and intention-to-treat analysis) were as follows: VAP incidence, 3.6% vs 5.3% (p = 0.2) and 3.8% vs 5.1%, respectively; incidence density, 17.9 vs 27.6 episodes per 1,000 days of mechanical ventilation (MV) [p = 0.18] and 18.9 vs 28.7 episodes per 1,000 days of MV, respectively; hospital antibiotic use in daily defined doses (DDDs), 1,213 vs 1,932 (p < 0.001) and 1,392 vs 1,932, respectively (p < 0.001). In patients who had received mechanical ventilation for > 48 h, the comparisons of CASS patients and control subjects were as follows: VAP incidence, 26.7% vs 47.5% (p = 0.04), respectively; incidence density, 31.5 vs 51.6 episodes per 1,000 days of MV, respectively (p = 0.03); median length of ICU stay, 7 vs 16.5 days (p = 0.01), respectively; hospital antibiotic use, 1,206 vs 1,877 DDD (p < 0.001), respectively; Clostridium difficile-associated diarrhea, 6.7% vs 12.5% (p = 0.3), respectively; and overall mortality rate, 44.4% vs 52.5% (p = 0.3), respectively. Reintubation increased the risk of VAP (relative risk [RR], 6.07; 95% confidence interval [CI], 2.20 to 16.60; p < 0.001), while CASS was the only significant protective factor (RR, 0.40; 95% CI, 0.16 to 0.99; p = 0.04). No complications related to CASS were observed. The cost of the CASS tube was 9 vs 1.5 euro for the conventional tube. CASS is a safe procedure that reduces the use of antimicrobial agents in the overall population and the incidence of VAP in patients who are at risk. CASS use should be encouraged, at least in patients undergoing MHS.